2020
DOI: 10.1111/jocn.15553
|View full text |Cite
|
Sign up to set email alerts
|

Emergency stress management among nurses: A lesson from the COVID‐19 outbreak in China–a cross‐sectional study

Abstract: Aims and objectives To assess the level of stress response, self‐efficacy and perceived social support status of working nurses during the outbreak of the COVID‐19 and investigate potential factors affecting their stress. Background The stress level of clinical nurses directly affects their physical and mental health and work efficiency. Design This study was a cross‐sectional investigation, which was performed following the STROBE checklist. The current study was conducted in February 2020 by selecting clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 27 publications
(27 reference statements)
4
30
2
Order By: Relevance
“…Receiving direct social support from friends, family, colleagues and supervisors was a key protective factor in all of the 19 studies that examined its association with psychological distress (Table 2). For example, in HCW during the COVID-19 outbreak, higher levels of social support were associated with significantly lower levels of stress, depression, anxiety, depression and PTSD (28,31,38,62,70,78,88,90,94,102,139,156). These findings were consistent with that of a study of frontline medical staff during the COVID-19 outbreak who reported that a positive attitude from co-workers was important for reducing their distress (39).…”
Section: Social Factorssupporting
confidence: 82%
See 1 more Smart Citation
“…Receiving direct social support from friends, family, colleagues and supervisors was a key protective factor in all of the 19 studies that examined its association with psychological distress (Table 2). For example, in HCW during the COVID-19 outbreak, higher levels of social support were associated with significantly lower levels of stress, depression, anxiety, depression and PTSD (28,31,38,62,70,78,88,90,94,102,139,156). These findings were consistent with that of a study of frontline medical staff during the COVID-19 outbreak who reported that a positive attitude from co-workers was important for reducing their distress (39).…”
Section: Social Factorssupporting
confidence: 82%
“…Fourteen studies examined how perceptions of control were associated with distress among HCW (Table 2). In eight studies, higher self-efficacy was associated with lower anxiety, depression, distress, and lower levels of fear about SARS and post-traumatic stress symptoms during the COVID-19 and SARS outbreaks, respectively (10,35,68,72,90,105,123,150). Conversely, feeling a loss of control was associated with greater distress (148) during the SARS outbreak in Hong Kong.…”
Section: Psychological Factorsmentioning
confidence: 98%
“…Health professionals have a higher risk of being infected with COVID-19 than other professions because the chances of being exposed to this virus are much greater in a hospital environment [17]. Based on the theory, self-management has a positive impact on the quality of one's health [18], [19], [20].…”
Section: Discussionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic has been an enormous challenge for healthcare worldwide, thus putting the mental health of healthcare workers at risk. The increased demand for care during the COVID-19 pandemic has significantly affected healthcare workers’ (HCWs) levels of stress [ 1 , 2 ], depression [ 3 , 4 ], and burnout [ 5 7 ] and posttraumatic stress disorder [ 8 ]. These mental health challenges might be also associated with an experience of moral injury which refers to psychological distress caused by particular actions or absence of them thus violating a person’s moral beliefs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%